Riddles: Perspectives on the use, function and change in a folklore genre - Kaivola-Bregenhøj, Annikki (Studia Fennica Folkloristica, 2001)
Riddles are a journey into a fascinating world rich in delightful metaphors and ambiguity. This book is based on material drawn from all over the world and analyses both traditional true riddles and contemporary joking questions. It introduces the reader to different riddling situations and the many functions of riddles, wich vary from education to teasing, and from defusing a heated situation to entertainment. In addition to providing a survey of international riddle scholarship, the book has a comprehensive bibliography with suggestions for further reading.